Telecommunication Value Network in Malaysia - Ong, Li Chien (2009)
Business network is believed to offer a superior way of managing the challenges related to the uncertainty and complexity of the contemporary business environment in Malaysia telecommunication industry. This study strives to analyze the value business network in Malaysia telecommunication industry with emphasize on the market leader, Maxis Communication Bhd in its mobile content services. The business network represents the form of organization where the focal company focuses on certain key activities and acquires other resources and skills through network relationships. These kinds of relationship are argues to increase flexibility, to offer the possibility to combine resources and skills with partners, and thereby to coevolve these capabilities between the members of the business network. Further, business networks are also believed to improve knowledge management and information processing capabilities.